Copper powder, conductive paste, low-temperature co-fired ceramic substrates and multilayer ceramic capacitors
By adding an appropriate amount of silicon and carbon to the copper powder and using -(OC)3H6)n and -(OC)2H4)n compounds, the sintering performance of copper powder is regulated, and the stress problems caused by shrinkage during sintering and insufficient sintering are solved, and the good sintering and conductivity of copper powder in low-temperature co-fired ceramic tiles and multi-layer capacitors are achieved.
Patent Information
- Application Number
- JP2023151688
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-04-14
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2043-09-19
AI Technical Summary
In the manufacturing process of low-temperature co-fired ceramic tiles and multi-layer capacitors, the rapid shrinkage of copper powder during sintering causes stress to the green sheet, which may lead to peeling between the sintered copper powder and ceramic powder and cracks in the sintered body. At the same time, insufficient sintering of copper powder will affect the surface smoothness and resistance.
Copper powder with a silicon content of 70 ppm or more and carbon content of 0.07% to 0.45% is used, which contains -(OC)3H6)n and -(OC)2H4)n classes of compounds during sintering, and these additives are used to regulate the shrinkage and sintering properties of the copper powder.
The copper powder shrinks relatively slowly during sintering, reducing stress on the green sheet, avoiding peeling and cracks after sintering, and improving the density and surface smoothness of the sintered body, ensuring good conductivity.
Smart Images

Figure 0007669439000003 
Figure 0007669439000004 
Figure 0007669439000001
Abstract
Description
[Technical field]
[0001] This specification discloses techniques relating to copper powder, conductive paste, low-temperature co-fired ceramic substrates, and multilayer ceramic capacitors. [Background technology]
[0002] In the manufacture of low temperature co-fired ceramics (LTCC) substrates and multilayer ceramic capacitors (MLCC), a conductive paste is applied to a green sheet and then fired at the same time, which sinters the ceramic powder in the green sheet and the metal powder in the conductive paste together.
[0003] The metal powders used in this case include silver powder and copper powder, for example. Of these, copper is cheaper than silver and is said to have less migration, so there is a demand for the development of copper powder suitable for LTCC substrates and MLCCs.
[0004] It is known that in order to improve adhesion between a conductive paste containing copper powder and a sintered ceramic body when the conductive paste is fired simultaneously with a green sheet, it is useful to increase the sintering start temperature of the copper powder. For example, Japanese Patent No. 5986117 (Patent Document 1) discloses a technique for increasing the sintering start temperature by mixing copper powder with an aminosilane aqueous solution and adsorbing the aminosilane onto the copper powder surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5986117 Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, a technique for increasing the adhesion between the copper powder and the ceramic sintered body by increasing the sintering start temperature of the copper powder has been known, but the present inventors have newly discovered that if the copper powder contained in the conductive paste shrinks quickly during sintering, the shrinkage behavior of the copper powder can cause large stress in the green sheet. This can lead to the copper powder sintered body peeling off from the ceramic powder sintered body after firing, or the sintered body cracking. For this reason, copper powder with a relatively slow shrinkage rate during sintering is sometimes required.
[0007] Furthermore, if the copper powder does not become a sufficiently dense sintered body after sintering, there is a concern that the surface smoothness of the sintered body will be impaired and the electrical resistance will increase. Therefore, it is desirable to improve the sinterability of the copper powder.
[0008] This specification provides a copper powder, a conductive paste, a low-temperature co-fired ceramic substrate, and a multilayer ceramic capacitor that shrink at a relatively slow rate during sintering and have excellent sinterability. [Means for solving the problem]
[0009] The copper powder disclosed in this specification has a silicon content of 70 mass ppm or more, a carbon content of 0.07 mass % or more and 0.45 mass % or less, and -(OC3H6) n Compounds having the structure - (n is 1 or more) and -(OC2H4) n The compound contains at least one of the compounds having the structure of - (n is 1 or more).
[0010] The conductive paste disclosed in this specification contains the above-mentioned copper powder.
[0011] The low-temperature co-fired ceramic substrate disclosed in this specification contains the above-mentioned sintered body of copper powder.
[0012] The multilayer ceramic capacitor disclosed in this specification contains the above-mentioned sintered body of copper powder. Effect of the Invention
[0013] The above copper powder shrinks at a relatively slow rate during sintering and has excellent sinterability. [Brief description of the drawings]
[0014] [Figure 1] 1 is a graph showing the change in linear expansion coefficient during heating in thermomechanical analysis of the copper powder of Example 2. [Diagram 2] 1 is a graph showing the change in linear expansion coefficient during heating in thermomechanical analysis of the copper powder of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, embodiments of the above-mentioned copper powder, conductive paste, low-temperature co-fired ceramic substrate, and multilayer ceramic capacitor will be described in detail.
[0016] In one embodiment, the copper powder has a silicon content of 70 mass ppm or more, a carbon content of 0.07 mass % or more and 0.45 mass % or less, and -(OC3H6) n Compounds having the structure - (n is 1 or more) and -(OC2H4) n The copper powder contains at least one of the compounds having the structure of - (n is 1 or more). This slows down the shrinkage rate during sintering of the copper powder and improves the sinterability of the copper powder. The reason for this is not entirely clear, but the results of the test described later in the Examples section showed such a tendency.
[0017] As a result, when the copper powder is used in the manufacture of LTCC substrates or MLCCs, the stress on the green sheet caused by the shrinkage of the copper powder in the conductive paste can be reduced, and peeling between the copper powder sintered body and the ceramic powder sintered body and the occurrence of cracks in the sintered body can be suppressed. In addition, the sintered body obtained after sintering the copper powder has high surface smoothness and is sufficiently dense to have excellent conductivity.
[0018] In order to slow down the shrinkage rate of the copper powder in the conductive paste during sintering, it is possible to mix glass frit into the conductive paste. However, in this case, if a certain amount of glass frit is mixed into the conductive paste in order to effectively slow down the shrinkage rate of the copper powder, the resistivity of the sintered body of the copper powder increases. In contrast, the copper powder of the above embodiment shrinks at a relatively slow rate during sintering, so the content of glass frit in the conductive paste can be reduced, and there are also cases where it is not necessary to include glass frit in the conductive paste. From this perspective, it can be said that the copper powder of the above embodiment can reduce the resistivity of the sintered body.
[0019] (copper powder) Copper powder contains copper (Cu) and is mostly composed of copper in many cases. The copper content of copper powder excluding copper oxide is, for example, 98% by mass or more, typically 99.5% by mass or more. The copper content of copper powder and the copper content can be confirmed and measured by X-ray diffraction (XRD).
[0020] The copper powder also contains silicon (Si). Silicon may be contained in the copper powder as a result of surface treatment of untreated copper powder with tetraethoxysilane (TEOS), for example, as in the manufacturing method described below.
[0021] The silicon content of the copper powder is 70 mass ppm or more, preferably 100 mass ppm or more. The copper powder contains silicon at such a content, and further has a predetermined carbon content, -(OC3H6) n Compounds having the structure - (n is 1 or more) and -(OC2H4) nWhen the composition contains at least one of the compounds having the structure of - (n is 1 or more), the effect of reducing the shrinkage rate during sintering and improving the sinterability can be obtained. On the other hand, if the silicon content is too high, the resistivity of the sintered body of the copper powder may become high. Therefore, the silicon content of the copper powder is preferably 2000 mass ppm or less, and more preferably 1500 mass ppm or less. The silicon content of the copper powder is determined by alkaline melting the copper powder using sodium peroxide and sodium carbonate, dissolving the resulting molten material with hydrochloric acid, and analyzing the solution to a certain amount by ICP optical emission spectroscopy (ICP-OES: PS3500UVDD2, manufactured by Hitachi High-Tech Science Corporation) to determine the mass (μg) of Si attached to the unit mass (g) of the surface-treated powder. The standard solutions used in the ICP-OES measurement are prepared to have concentrations of 0, 0.1, and 1.0 μg / mL, respectively, to form a calibration curve, and the concentration in the sample is adjusted to be within this range. The amount of sample taken is 0.5 g. The standard solution can be made by matching sodium peroxide, sodium carbonate, and hydrochloric acid to the same concentration as the sample solution. The measurement wavelength is the emission line near 251.687 nm, and the background is 0.020 nm on the long wavelength side and 0.016 nm on the short wavelength side from the peak top.
[0022] Copper powder also contains carbon (C). As described below, untreated copper powder contains -(OC3H6) n - (n is 1 or more), and / or -(OC2H4) n When surface treatment is performed using compounds having the structure - (n is 1 or more), carbon is included in the copper powder due to these compounds. -(OC3H6) n Examples of compounds having the structure of - include propylene glycol (PG) and polypropylene glycol (PPG). PPG is -(OC3H6) n - is a polymer with a repeating structure of -(OC2H4) nExamples of compounds having the - structure include ethylene glycol (EG) and polyethylene glycol (PEG). PEG has the structure -(OC2H4) n - is a polymer having a repeating structure.
[0023] In order to effectively reduce the shrinkage rate during sintering of copper powder and increase its sinterability, it is desirable for the copper powder to contain a certain amount of carbon. However, if the carbon content is too high, there is a concern that the sinterability of the copper powder will be insufficient and the electrical conductivity of the sintered body of the copper powder will be insufficient. Therefore, the carbon content of the copper powder is 0.07% by mass or more and 0.45% by mass or less, preferably 0.1% by mass or more and 0.40% by mass or less.
[0024] The carbon content of copper powder is measured by high-frequency induction heating furnace combustion-infrared absorption method. Specifically, the carbon content of copper powder can be measured using a carbon-sulfur analyzer such as LECO CS844 type, with the sample amount adjusted to be within the calibration curve intensity range, LECO CEL II and Fe chips as combustion improvers, and a steel pin as a standard material for the calibration curve. The sample was placed in an alumina crucible and measured. The alumina crucible was pretreated in advance by heating it from room temperature to 1000°C in air at a constant heating rate over 2 hours and then holding it at 1000°C for 2 hours before being used to measure the carbon content of the copper powder.
[0025] The mass ratio of the carbon content to the silicon content of the copper powder is preferably 7 or more, and more preferably 10 or more. This makes it possible to further slow down the shrinkage rate during sintering of the copper powder. The mass ratio can be calculated by "carbon content (mass%) ÷ (silicon content (mass ppm) ÷ 10000)".
[0026] Copper powder is also -(OC3H6) n - and / or -(OC2H4) nIn addition, if the copper powder has a certain silicon and carbon content, the shrinkage rate during sintering is effectively reduced and the sinterability is improved. n -Ya-(OC2H4) n In -, n may be, for example, an integer from 1 to 10, or even from 11 to 100. The above compounds may be contained in the copper powder due to at least one of the compounds PG, PPG, EG, and PEG, which are components of the surface treatment applied to untreated copper powder during the production of the copper powder. Typically, copper powder contains PPG, i.e., H[OCH(CH3)CH2] n OH, R1OCH2CH(OR2)CH2OR3(R1=[CH2CH(CH3)O] x H, R2 = [CH2CH(CH3)O] y H, R3 = [CH2CH(CH3)O] z H, x+y+z=n, n=1-100). The copper powder may also contain PEG, i.e., HO(CH2CH2O) n Compounds represented by H may be included.
[0027] Copper powder is -(OC3H6) n - and compounds with the structure -(OC2H4) nTo confirm whether the compound having the structure of - is contained, a liquid chromatography-Orbitrap mass spectrometer (manufactured by Thermo Fisher Scientific, LC-Orbitrap MS, LC: Vanquish analytical purification LC system, Orbitrap MS: Orbitrap Exploris240 mass spectrometer) can be used. The measurement conditions are as follows. Copper powder is placed in a solution (volume ratio 1:1) of 10 mmol / L ammonium acetate aqueous solution and acetonitrile (4 mL of mixed solvent for 1 g of copper powder), stirred with a shaker and an ultrasonic cleaner, and separated into copper powder and extract by centrifugation, and the extract is collected by syringe filter filtration (manufactured by Merck Millipore, Millex (registered trademark)-LCR, material: hydrophilic PTEF, pore size: 0.45 μm). This extract is measured with the above-mentioned liquid chromatography-Orbitrap mass spectrometer. The column is Hypersil GOLD (C18), the mobile phase is changed from 10 mmol / L ammonium acetate aqueous solution to acetonitrile, and the column temperature is 40°C. As an example, copper powder is -(OC3H6) n In the case of a polymer (e.g., PPG) having a repeating structure of -, peaks with m / z values spaced 58 apart can be detected in positive ion detection mode. In addition, copper powder is -(OC2H4) n When the copper powder contains a polymer having a repeating structure of - (e.g., PEG), peaks with m / z values spaced at 44 intervals can be detected in positive ion detection mode. When the copper powder contains PG represented by HO(C3H6O)H, a peak with m / z value of 76 can be detected in positive ion detection mode. When the copper powder contains R1OCH2CH(OR2)CH2OR3 (R1=[CH2CH(CH3)O] x H, R2 = [CH2CH(CH3)O] y H, R3 = [CH2CH(CH3)O] zWhen the copper powder contains PG represented by the formula (x+y+z=1), a peak with an m / z value of 150 can be detected in the positive ion detection mode. When the copper powder contains EG, a peak with an m / z value of 62 can be detected in the positive ion detection mode.
[0028] The copper powder as described above preferably has a 90% shrinkage temperature of 700° C. or higher when heated from room temperature to 1000° C. by thermomechanical analysis (TMA). The sintering end temperature of such copper powder with a high 90% shrinkage temperature may be close to the sintering end temperature of the ceramic powder used in the manufacture of LTCC substrates or MLCCs, and peeling of the ceramic powder from the sintered body and the occurrence of cracks after sintering can be more effectively suppressed.
[0029] Furthermore, it is preferable that the 10% shrinkage temperature of the copper powder when heated from room temperature to 1000° C. by thermomechanical analysis is 400° C. or higher. In this case, the sintering start temperature of the copper powder becomes close to the sintering start temperature of the ceramic powder, and it is expected that the occurrence of peeling and cracks in the sintered body will be more effectively suppressed.
[0030] Specifically, the thermomechanical analysis is carried out as follows. That is, copper powder (about 0.3 g) is placed in a pellet die with a hole of 5 mm in diameter, and compressed with a force of 1 kN to produce a cylindrical copper powder pellet (height: about 3 mm, diameter: about 5 mm). The height is measured with a micrometer (Mitutoyo, coolant-proof micrometer MDC-25MX, maximum allowable error ±1 μm), and this is taken as the initial pellet height. This pellet is set in a thermomechanical analyzer (NETZSCH, TMA4000SE), evacuated to -0.1 MPa or less, and then N2 is introduced to create an inert atmosphere. While flowing N2 at a flow rate of 500 mL / min, the temperature is raised from room temperature (25°C) to 1000°C at a heating rate of 10°C / min while applying a load of 10 g weight. During this heating from 40°C to 1000°C, the pellet height is measured every second, and the temperature at which it shrinks by 10% of the maximum shrinkage width from the initial pellet height to the minimum pellet height is the 10% shrinkage temperature, and the temperature at which it shrinks by 90% is the 90% shrinkage temperature. For example, if the initial pellet height is 3mm and the minimum pellet height when heated to 1000°C is 2mm, the temperature at which the pellet height first becomes 2.9mm is the 10% shrinkage temperature, and the temperature at which the pellet height first becomes 2.1mm is the 90% shrinkage temperature.
[0031] In addition, it is preferable that the minimum value of the linear expansion coefficient of the copper powder during heating from room temperature to 1000°C in thermomechanical analysis is 90% or more of the theoretical ideal linear expansion coefficient calculated from the true density and thermal expansion coefficient of copper at the temperature at which the minimum value is obtained. In the above-mentioned thermomechanical analysis, the linear expansion coefficient is calculated by dividing the pellet height of the copper powder pellet during heating by the initial pellet height, subtracting 1 from the value, and then multiplying it by 100. Since the pellet height decreases during heating, the linear expansion coefficient becomes a negative value. The copper powder pellet shrinks with heating, and the linear expansion coefficient changes accordingly with heating. When the linear expansion coefficient becomes minimum during heating from room temperature to 1000°C, the copper powder pellet can be considered to have been sintered most and contracted the most. If this minimum value of the linear expansion coefficient is close to the theoretical ideal linear expansion coefficient of lump copper at the temperature at which the minimum value is obtained, the copper powder can be said to have particularly excellent sinterability. The theoretical ideal linear expansion coefficient is calculated by dividing the true density of copper (8.96 g / cm 3 ) and thermal expansion coefficient (1.77×10 -5 By calculating the linear expansion coefficient of an object having the same size and shape as the copper powder pellet from the linear expansion coefficient (K) of the copper powder pellet, the value that changes with temperature can be calculated.
[0032] The BET specific surface area of copper powder is, for example, 1 m 2 / g~15m 2 / g, typically 3m 2 / g~7m 2 / g. The BET specific surface area of copper powder can be measured in accordance with JIS Z8830:2013 using a Microtrack-Bell BELSORP-mini II. More specifically, a 3 g sample of copper powder is degassed for 5 hours at 70°C in a vacuum with an absolute pressure of 10 Pa or less, and then the nitrogen adsorption isotherm is measured by the static volumetric method, and the results are analyzed by the BET method to calculate the BET specific surface area. In addition, as the BET specific surface area of copper powder increases, the surface energy of the copper powder increases, which is expected to result in a decrease in the sintering temperature, but it is thought that this will not affect the shrinkage rate during sintering.
[0033] The above-mentioned copper powder can be produced by subjecting untreated copper powder to a surface treatment using TEOS and at least one compound selected from the group consisting of PG, PPG, EG, and PEG, and adhering each of these compounds to the surface treatment. By this surface treatment, the copper powder is converted into silicon derived from TEOS, carbon derived from the above compounds, and -(OC3H6) n - and / or -(OC2H4) n In addition, TEOS is also known as tetraethyl orthosilicate, and is a compound represented by Si(OC2H5)4.
[0034] In the surface treatment with TEOS, for example, copper powder can be added to a TEOS aqueous solution, stirred or kneaded, and then dried and crushed. In the surface treatment with PG or PPG, copper powder can be added to a PG aqueous solution or a PPG aqueous solution, mixed, stirred or kneaded, dried, and crushed. In the surface treatment with EG or PEG, copper powder can be added to an EG aqueous solution or a PEG aqueous solution, mixed, stirred or kneaded, dried, and crushed. The surface treatment with TEOS, the surface treatment with PG, the surface treatment with PPG, the surface treatment with EG, and / or the surface treatment with PEG can be performed in any order, and any surface treatment can be performed first. In addition, copper powder can be added to an aqueous solution containing TEOS and at least one of PG, PPG, EG, and PEG, and each surface treatment can be performed simultaneously. By appropriately adjusting the amount of each compound in the aqueous solution, copper powder with the desired silicon content and carbon content can be produced. From the viewpoint of making the silicon content of the finally obtained copper powder 70 mass ppm to 2000 mass ppm, the amount of TEOS added to the aqueous solution can be 0.52 mg to 22.59 mg per 1 g of copper powder contained in the aqueous solution. Similarly, from the viewpoint of making the carbon content of the finally obtained copper powder 0.07 mass % to 0.45 mass %, the amount of PPG added to the aqueous solution can be 0.52 mg to 22.59 mg per 1 g of copper powder contained in the aqueous solution. nFor the PPG diol type represented by H, the carbon content varies depending on the degree of polymerization. For example, for 1 g of copper powder in the aqueous solution, when the degree of polymerization is 1 (i.e., when the PG has a molecular weight of 62), the carbon content is 1.48 to 9.50 mg, when the degree of polymerization is 10, the carbon content is 1.16 to 7.48 mg, when the degree of polymerization is 100, the carbon content is 1.13 to 7.28 mg, and when the degree of polymerization is 100, the carbon content is 1.06 to 1.24 mg. x H, R2 = [CH2CH(CH3)O] y H, R3 = [CH2CH(CH3)O] z For the PPG triol type represented by the formula (H, x+y+z=n, n=1-100), the carbon content varies depending on the degree of polymerization. For example, when the degree of polymerization is 1 (i.e., when the PG has a molecular weight of 150), the carbon content can be 1.46-9.38 mg, when the degree of polymerization is 10, the carbon content can be 1.19-7.64 mg, and when the degree of polymerization is 100, the carbon content can be 1.13-7.38 mg. Also, the carbon content of PEG varies depending on the degree of polymerization. Therefore, for example, when the degree of polymerization of PEG is 1, the amount of PEG added to the aqueous solution can be 1.81 mg-11.63 mg per 1 g of copper powder contained in the aqueous solution, from the viewpoint of making the carbon content of the copper powder finally obtained 0.07% by mass-0.45% by mass. Also, when the degree of polymerization of PEG is 10, the amount of PEG added to the aqueous solution can be 1.34 mg-8.59 mg per 1 g of copper powder contained in the aqueous solution. Furthermore, when the degree of polymerization of PEG is 100, the amount of PEG added to the aqueous solution can be 1.29 mg to 8.29 mg per gram of copper powder contained in the aqueous solution.
[0035] The untreated copper powder to be subjected to the above surface treatment may be obtained by purchasing, or may be prepared by generating copper particles by a liquid phase method such as a chemical reduction method or a disproportionation method as described below.
[0036] In the chemical reduction method, for example, a copper salt aqueous solution such as a copper sulfate aqueous solution is used as a raw solution, and after adjusting the pH by adding sodium hydroxide or other alkali, a reducing agent such as hydrazine is added to generate cuprous oxide powder in the slurry based on a reduction reaction such as 4CuSO4+N2H4+8NaOH→2Cu2O+4Na2SO4+6H2O+N2. Next, this slurry is heated and while adjusting the pH, hydrazine is further added to reduce the cuprous oxide to copper through a reaction such as 2Cu2O+N2H4→4Cu+2H2O+N2, generating copper particles in the liquid.
[0037] In the disproportionation method, for example, an aqueous solution containing a dispersant such as gum arabic, gelatin, or collagen peptide is mixed with a slurry containing cuprous oxide powder, and sulfuric acid is added to the mixture to produce copper particles in the liquid through the disproportionation reaction Cu2O+H2SO4→Cu↓+CuSO4+H2O.
[0038] The term "untreated copper powder" used herein refers to copper powder that has not yet been subjected to surface treatment with TEOS, PG, PPG, EG, or PEG. The untreated copper powder may be copper powder that has already been subjected to a treatment other than the surface treatment with TEOS, PG, PPG, EG, or PEG after the production of copper particles.
[0039] (Conductive paste) The conductive paste contains the copper powder described above. This conductive paste may contain the copper powder described above, a binder resin, and a solvent.
[0040] Examples of the binder resin include cellulose resin, acrylic resin, alkyd resin, polyvinyl alcohol resin, polyvinyl acetal, ketone resin, urea resin, melamine resin, polyester, polyamide, and polyurethane.
[0041] Examples of the solvent that can be used include alcohol solvents (e.g., one or more selected from the group consisting of terpineol, dihydroterpineol, isopropyl alcohol, butyl carbitol, terpineloxyethanol, and dihydroterpineloxyethanol), glycol ether solvents (e.g., butyl carbitol), acetate solvents (e.g., one or more selected from the group consisting of butyl carbitol acetate, dihydroterpineol acetate, dihydrocarbitol acetate, carbitol acetate, linalyl acetate, and terpinyl acetate), ketone solvents (e.g., methyl ethyl ketone), hydrocarbon solvents (e.g., one or more selected from the group consisting of toluene and cyclohexane), cellosolves (e.g., one or more selected from the group consisting of ethyl cellosolve and butyl cellosolve), diethyl phthalate, and propionate solvents (e.g., one or more selected from the group consisting of dihydroterpineol propionate, dihydrocarbyl propionate, and isobornyl propionate).
[0042] (LTCC substrate and MLCC) To manufacture an LTCC substrate or an MLCC, for example, in the co-firing method, the above-mentioned conductive paste can be applied by printing or the like onto a green sheet containing ceramic powder, and the conductive paste and the green sheet can be alternately stacked and then fired simultaneously.
[0043] The LTCC substrates and MLCCs manufactured in this manner contain a sintered body of the copper powder contained in the conductive paste.
[0044] Here, by using the copper powder of the above-mentioned embodiment in the conductive paste, it is possible to effectively suppress the occurrence of peeling between the conductive paste and the green sheet, and the occurrence of cracks in the sintered body of the copper powder or ceramic powder. In this case, the sintered body of the copper powder obtained after firing is dense and has a smooth surface. As a result, the sintered body of such copper powder can be used to form copper wiring with high conductivity. EXAMPLES
[0045] Next, the above-mentioned copper powder was produced as a prototype, and its effects were confirmed, which will be described below. However, the description here is merely for illustrative purposes and is not intended to be limiting.
[0046] <Test Example 1> Example 1 The specific surface area is 2.0m 2 0.92 g of a 5 mass% TEOS aqueous solution was added to 25 g of untreated copper powder having a molecular weight of 1000 g / g, and 2 g of pure water was added. The mixture was kneaded in a planetary centrifugal mixer (model: ARE-310, manufactured by Thinky Corporation) with revolution speed of 2000 rpm, rotation speed of 800 rpm, and kneading time of 5 minutes. After kneading, the slurry was collected and vacuum dried (-0.1 MPa or less) in a vacuum dryer (model: AVO-250-SB, manufactured by AS ONE Corporation) at a temperature of 70°C for 5 hours. After vacuum drying, it was confirmed that the temperature had dropped, and the mixture was crushed in a mortar to obtain copper powder A. This copper powder A is the same as the copper powder in Comparative Example 3 described later.
[0047] In addition, 5 g of polypropylene glycol 300 (triol type, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., hereinafter referred to as PPG) was added to 45 g of pure water to prepare a 10% by mass PPG aqueous solution. 2 To 25 g of untreated copper powder having a molecular weight of 1.0 to 1.0 kg / g, 2.5 g of a 10 mass % PPG aqueous solution was added, and then 2 g of pure water was added, followed by the same kneading, vacuum drying, and crushing as above to obtain copper powder B. This copper powder B is the same as the copper powder in Comparative Example 2 described below.
[0048] The copper powder A and the copper powder B were mixed in a mortar in a weight ratio of 1:1 to obtain the copper powder of Example 1.
[0049] Example 2 The copper powder A and the copper powder B were mixed in a weight ratio of 2:1 using a mortar to obtain the copper powder of Example 2.
[0050] Example 3 The specific surface area is 2.0m 20.61 g of a 5 mass% TEOS aqueous solution and 0.83 g of a 10 mass% PPG aqueous solution were added to 25 g of untreated copper powder having a molecular weight of 1.0 g / g, and 2 g of pure water was further added. After that, the same kneading, vacuum drying, and crushing as in Example 1 were performed to obtain copper powder.
[0051] Example 4 The specific surface area is 2.0m 2 The same procedure as in Example 3 was carried out, except that 0.77 g of a 5 mass % TEOS aqueous solution and 0.42 g of a 10 mass % PPG aqueous solution were added to 25 g of untreated copper powder having a molecular weight of 1.01 g / g.
[0052] Example 5 The specific surface area is 2.0m 2 The same procedure as in Example 3 was carried out, except that 0.83 g of a 5 mass % TEOS aqueous solution and 0.23 g of a 10 mass % PPG aqueous solution were added to 25 g of untreated copper powder having a molecular weight of 1.01 g / g.
[0053] Example 6 The specific surface area is 2.0m 2 The same procedure as in Example 3 was carried out, except that 0.69 g of a 5 mass % TEOS aqueous solution and 0.625 g of a 10 mass % PPG aqueous solution were added to 25 g of untreated copper powder having a molecular weight of 1.01 g / g.
[0054] Example 7 The specific surface area is 1.7m 2 9.54 g of PPG and 17.65 g of 20 mass% TEOS aqueous solution were added to 6220 g of a slurry (water content: 53.48 mass%) of untreated copper powder having a molecular weight of 100 / g and pure water, and the mixture was stirred for 15 minutes to obtain a surface-treated copper slurry. The surface-treated copper slurry was dried, air-disintegrated, and vacuum-dried to obtain copper powder.
[0055] Comparative Example 1 The specific surface area is 2.0m 2 The same procedure as in Example 3 was carried out except that only 1.25 g of a 10 mass % PPG aqueous solution was added to 25 g of untreated copper powder having a molecular weight of 1.01 g / g, and no TEOS aqueous solution was added.
[0056] Comparative Example 2 This is copper powder B of Example 1.
[0057] Comparative Example 3 This is copper powder A of Example 1.
[0058] Comparative Example 4 The specific surface area is 1.7m 2 / g, and was not surface-treated with TEOS or PPG.
[0059] Comparative Example 5 The specific surface area is 1.7m 2 19.34 g of PPG was added to 4025 g of a slurry (water content: 52.03 mass%) made by mixing untreated copper powder having a molecular weight of 100 / g with pure water, and the mixture was stirred for 15 minutes to obtain a surface-treated copper slurry. The surface-treated copper slurry was dried, air-disintegrated, and vacuum-dried to obtain copper powder.
[0060] Comparative Example 6 The specific surface area is 2.0m 2 The same procedure as in Example 3 was carried out, except that 0.08 g of a 5 mass % TEOS aqueous solution and 2.27 g of a 10 mass % PPG aqueous solution were added to 25 g of untreated copper powder having a molecular weight of 1.01 g / g.
[0061] Comparative Example 7 The specific surface area is 3.0m 2 The same procedure as in Comparative Example 1 was carried out, except that untreated copper powder having a copper content of 0.01 wt. / g was used.
[0062] (evaluation) The silicon content, carbon content, and BET specific surface area of each of the copper powders were measured by the methods described above. The results are shown in Table 1.
[0063] The silicon content of the copper powders of Comparative Examples 1, 2, and 7 was not measured, but it is assumed to be sufficiently low since the surface treatment with TEOS was not performed. The silicon content and carbon content of the copper powders of Examples 1 and 2 were not measured, and values calculated from the mixing ratio of copper powder A (Comparative Example 3) and copper powder B (Comparative Example 2), the silicon content of Comparative Example 3, and the carbon content of Comparative Example 2 are shown in Table 1. Specifically, the carbon content of copper powder A (Comparative Example 3) was estimated based on the mixing ratio, assuming that the silicon content of copper powder B (Comparative Example 2) was 0 mass% and that the silicon content of copper powder B (Comparative Example 2) was 0 mass ppm. For example, in Example 2, copper powder A and copper powder B were mixed at a mass ratio of 2:1, so the carbon content was estimated as "((carbon content of copper powder A) x 2 + (carbon content of copper powder B) x 1) / 3".
[0064] In addition, the BET specific surface area of the copper powder after surface treatment was not measured except for the examples and comparative examples whose BET values are shown in Table 1. However, it was separately confirmed that the BET specific surface area after the surface treatment was not significantly different from that before the surface treatment. Specifically, the specific surface area of the copper powder in Example 7 was 1.67 m 2 / g, whereas the specific surface area of the copper powder before surface treatment is 1.71 m 2 / g.
[0065] In addition, each copper powder is -(OC3H6) n Although it was not actually confirmed whether the copper powders in Examples 1 to 7 and Comparative Examples 1, 2, and 5 to 7 contained a compound having the structure of -(OC3H6) n Since the surface treatment is performed using PPG, which has the structure of -, when confirmed by the above-mentioned method, -(OC3H6) n -It is highly likely that the structure is
[0066] Thermomechanical analysis was also performed according to the method described above, and the analysis results shown in Table 1 were obtained. In Table 1, "percentage relative to ideal shrinkage" refers to the percentage of the minimum linear expansion coefficient relative to the theoretically ideal linear expansion coefficient, and in "sinterability," a percentage of 90% or more is marked "good," and a percentage of less than 90% is marked "bad." Note that in Table 1, some of the above percentages exceed 100%, but this is believed to be due to error. A specific method for calculating the theoretical ideal linear expansion coefficient of copper in thermomechanical analysis will be described using Example 2. In Example 2, the initial pellet had a height of 2.861 mm, a diameter of 5.000 mm, and a weight of 0.3014 g. Since the pellet was cylindrical, the density was 5.37 g / cm 3 If the height and diameter of the copper powder pellet are assumed to shrink at the same rate, the true density of copper (8.96 g / cm 3 ), the linear expansion coefficient must reach -15.7%, at which point the height is calculated to be 2.412 mm, the diameter to be 4.215 mm, and the weight to be 0.3014 g. This is the size of the fully sintered body at room temperature (25°C). A fully sintered body is a sintered body that is free of impurities such as voids or surface treatment agents and has the same density as the true density of copper. Since the pellets expand due to heat, the pellet height of the fully sintered body at the temperature at which sintering had progressed most in the TMA measurements (895°C) was calculated using the thermal expansion coefficient of copper (1.77 x 10 -5 When the linear expansion coefficient is calculated taking into account the thermal expansion coefficient (Tc) of the pellet, the linear expansion coefficient is -14.4% when the pellet height changes from the initial 2.861 mm to the fully sintered pellet height of 2.449 mm, so the theoretically ideal linear expansion coefficient at 895°C is -14.4%.
[0067] In Table 1, "shrinkage rate" is a graph showing the change in linear expansion coefficient versus temperature obtained by thermomechanical analysis, and represents the slope of the line connecting the plots of 10% shrinkage temperature and 90% shrinkage temperature. Copper powders with absolute values of shrinkage rate less than 0.5% / ℃ can be said to have a sufficiently gentle shrinkage rate during sintering.
[0068] The copper powders in Examples 1 to 7 were surface-treated with both TEOS and PPG, had a predetermined silicon content and carbon content, and were -(OC3H6) n - structure. As a result, as shown in Table 1, all of the copper powders of Examples 1 to 7 had good sinterability, and the absolute value of the shrinkage rate was small in all cases, so it was recognized that they shrink at a relatively slow rate during sintering. Furthermore, from the results of Examples 3 to 7 in which the surface treatments with TEOS and PPG were performed simultaneously, it was recognized that the greater the mass ratio of the carbon content to the silicon content of the copper powder, the smaller the absolute value of the shrinkage rate tends to be.
[0069] On the other hand, the copper powders of Comparative Examples 1, 2 and 7, which were only surface-treated with PPG, had poor sinterability. In Comparative Example 6, both TEOS and PPG were surface-treated, but the amount of TEOS was too small, so the copper powder contained almost no silicon and had poor sinterability. The copper powders of Comparative Examples 3 and 4, which were only surface-treated with TEOS or were not surface-treated with either, had a high shrinkage rate.
[0070] For reference, graphs showing the change in linear expansion coefficient for each copper powder of Example 2 and Comparative Example 2 are shown in Figures 1 and 2, respectively. In the graphs, the dashed line shows the temperature change of the theoretically ideal linear expansion coefficient. From Figure 1, it can be seen that the copper powder of Example 2 has a slow shrinkage rate during sintering and excellent sinterability. On the other hand, from Figure 2, it can be seen that the copper powder of Comparative Example 2 has a slow shrinkage rate during sintering but insufficient sinterability.
[0071] [Table 1]
[0072] <Test Example 2> Example 1 The specific surface area is 1.9m 20.92 g of a 5 mass% TEOS aqueous solution was added to 25 g of untreated copper powder having a molecular weight of 1000 g / g, and 2 g of pure water was added. The mixture was kneaded in a planetary centrifugal mixer (model: ARE-310, manufactured by Thinky Corporation) with revolution speed of 2000 rpm, rotation speed of 800 rpm, and kneading time of 5 minutes. After kneading, the slurry was collected and vacuum dried (-0.1 MPa or less) in a vacuum dryer (model: AVO-250-SB) with a setting of maintaining a state of 70°C for 5 hours. After vacuum drying, it was confirmed that the temperature had dropped, and the mixture was crushed in a mortar to obtain copper powder A. This copper powder A is the same as the copper powder in Comparative Example 1 described later.
[0073] In addition, 5 g of polyethylene glycol 400 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., hereinafter referred to as PEG) was added to 45 g of pure water to prepare a 10% by mass aqueous solution of PEG. 2 To 25 g of untreated copper powder having a molecular weight of 1.0 to 1.0 kg / g, 2.5 g of a 10 mass% aqueous PEG solution was added, and 2 g of pure water was further added. Thereafter, the same kneading, vacuum drying, and crushing were performed as above to obtain copper powder B. This copper powder B is the same as the copper powder in Comparative Example 2 described below.
[0074] The copper powder A and the copper powder B were mixed in a weight ratio of 5:5 using a mortar to obtain the copper powder of Example 1.
[0075] Example 2 The copper powder A and the copper powder B were mixed in a weight ratio of 7:3 using a mortar to obtain the copper powder of Example 2.
[0076] Example 3 The copper powder A and the copper powder B were mixed in a weight ratio of 9:1 using a mortar to obtain the copper powder of Example 3.
[0077] Comparative Example 1 This is copper powder A of Example 1.
[0078] Comparative Example 2 This is copper powder B of Example 1.
[0079] Comparative Example 3 The copper powder A and the copper powder B were mixed in a weight ratio of 1:9 using a mortar to obtain the copper powder of Comparative Example 3.
[0080] (evaluation) The silicon content, carbon content, and BET specific surface area of each of the copper powders were measured by the methods described above. The results are shown in Table 2.
[0081] The silicon content of the copper powder of Comparative Example 2 was not measured, but it is assumed to be sufficiently low since no surface treatment with TEOS was performed. The silicon content and carbon content of the copper powder of Examples 1 to 3 and Comparative Example 3 were not measured, and values calculated from the mixing ratio of copper powder A (Comparative Example 1) and copper powder B (Comparative Example 2), the silicon content of Comparative Example 1, and the carbon content of Comparative Example 2 are shown in Table 2. Specifically, the silicon content of copper powder B (Comparative Example 2) was estimated based on the mixing ratio, assuming that it was 0 ppm by mass.
[0082] In addition, the BET specific surface area of the copper powder after the surface treatment was not measured except for the comparative examples whose BET values are shown in Table 2. However, as described above, it was separately confirmed that the BET specific surface area after the surface treatment was not significantly different from that before the surface treatment.
[0083] In addition, each copper powder is -(OC2H4) n Although it was not actually confirmed whether the copper powders in Examples 1 to 3 and Comparative Examples 2 and 3 contained a compound having the structure of -(OC2H4) n Since the surface treatment was performed using PEG with the - structure, when confirmed by the above-mentioned method, -(OC2H4) n -It is highly likely that the structure is
[0084] Further, thermomechanical analysis was performed according to the method described above, and the analysis results shown in Table 2 were obtained. Table 2 shows the results of thermomechanical analysis obtained in the same manner as in Test Example 1.
[0085] The copper powders in Examples 1 to 3 were surface-treated with both TEOS and PEG, had a predetermined silicon content and carbon content, and had a -(OC2H4)n As a result, as shown in Table 2, all of the copper powders of Examples 1 to 3 had good sinterability, and the absolute value of the shrinkage rate was small in all cases, indicating that they shrink at a relatively slow rate during sintering.
[0086] On the other hand, the copper powder of Comparative Example 1, which was only surface-treated with TEOS, had a high shrinkage rate. Also, the copper powder of Comparative Example 2, which was only surface-treated with PEG, and the copper powder of Comparative Example 3, which had a low ratio of copper powder A, had poor sinterability.
[0087] [Table 2]
[0088] From the above, it was suggested that the above-mentioned copper powder shrinks at a relatively slow rate during sintering and has excellent sinterability. Furthermore, from the results of Test Examples 1 and 2, since either "a compound having the -(OC3H6)n- structure" or "a compound having the -(OC2H4)n- structure" has an effect, it is naturally inferred that copper powder containing both "a compound having the -(OC3H6)n- structure and a compound having the -(OC2H4)n- structure", which includes both, also has the specified effect.
Claims
1. The silicon content is 70 mass ppm or more, the carbon content is 0.07 mass % or more and 0.45 mass % or less, and -(OC 3 H 6 ) n Compounds having the structure of - (n is 1 or more) and -(OC 2 H 4 ) n The copper powder contains at least one compound selected from the group consisting of compounds having the structure of - (n is 1 or more).
2. 2. The copper powder according to claim 1, wherein the mass ratio of the carbon content to the silicon content is 7 or more.
3. - (OC 3 H 6 ) n Polymers having a repeating unit of - and -(OC 2 H 4 ) n 3. The copper powder according to claim 1, further comprising at least one polymer having a repeating structure of -.
4. Copper powder as described in claim 1 or 2, wherein the compound having the structure -(OC 3 H 6 ) n - (n is 1 or more) and the compound having the structure -(OC 2 H 4 ) n - (n is 1 or more) contain at least one compound selected from the group consisting of propylene glycol, polypropylene glycol, ethylene glycol and polyethylene glycol.
5. 3. The copper powder according to claim 1, which has a 90% shrinkage temperature of 700°C or higher when heated from room temperature to 1000°C by thermomechanical analysis (TMA).
6. 3. The copper powder according to claim 1, which has a 10% shrinkage temperature of 400° C. or higher when heated from room temperature to 1,000° C. by thermomechanical analysis (TMA).
7. 3. The copper powder according to claim 1 or 2, wherein the minimum value of the linear expansion coefficient during heating from room temperature to 1000°C by thermomechanical analysis (TMA) is 90% or more of the theoretical ideal linear expansion coefficient calculated from the true density and thermal expansion coefficient of copper at the temperature at which the minimum value is obtained.
8. BET specific surface area is 1m 2 / g to 15m 2 The copper powder according to claim 1 or 2, wherein the copper powder has a molecular weight of 1000 or more and a molecular weight of 1000 or more.
9. A conductive paste comprising the copper powder according to claim 1 or 2.
10. A low-temperature co-fired ceramic substrate comprising a sintered body of the copper powder according to claim 1 or 2.
11. A multilayer ceramic capacitor comprising a sintered body of the copper powder according to claim 1 or 2.
Citation Information
Patent Citations
Light emitting display unit
JP1984086117A
Copper powder with coating layer and production method thereof
JP2023005809A